MP14: Quantification of head-neck motion in trauma patients in the emergency department under spinal motion restriction: a prospective observational study. (May 2020) - Kulas, M.; Brueton-Campbell, L.; Weldon, E.; McDonald, N.; Pryce, R.
Abstract : Introduction: This was a prospective observational study involving a convenience sample of low-risk trauma patients presenting to a Level 1 Trauma Centre under spinal motion restriction (SMR). To our knowledge no prior studies have objectively measured head-neck (H-N) motion in trauma patients with suspected spine injuries during emergency department (ED) care. The goal was to establish the feasibility of deploying non-invasive motion sensors on trauma patients in the ED and to provide initial estimates for H-N kinematics under SMR during different phases of treatment. Methods: Low-risk adult patients treated by Winnipeg Fire Paramedic Service who sustained non-life threatening trauma with the potential for spine injury were eligible for inclusion. Participants received usual pre-hospital care; application of spine board and/or cervical collar, as determined by local practice protocol. Inertial measurement units (IMUs) were placed on participant's forehead, sternum and stretcher upon arrival to the ED. Data was collected during three phases of care: patient handling (log rolls, transfers, clothing removal); stretcher movement (to imaging, etc); stretcher stationary. IMUs were removed upon disposition decision by the attending physician. IMUs yielded data on H-N motion in terms of linear acceleration (resultant) and angular displacement (rotation + flexion-extension + side-flexion = total). Peak (M +/- SE) displacements and accelerations are reported, with comparisons across treatment phases using repeated measures ANOVA. Results: Eleven patients were enrolled in the study (age: 49 +/- 16 years; Injury Severity Score 13.4 +/- 9.9; female = 2). Substantial H-N motion was observed during ED care. Total H-N displacement (28.6 +/- 3.6 deg) and acceleration (7.8 +/- 1.0 m/s2) were higher during patient handling compared to stretcher moving (13.0 +/- 2.5 deg; 4.6 +/- 0.9 m/s2; p < .05) but not while the stretcher was stationary (18.9 +/- 3.4 deg; 5.4 +/- 1.2 m/s2; p > .06). Similar differences were detected for side-flexion and flexion-extension (p < .05), with peak displacements of 11.4+/-1.5 deg and 14.6 +/- 2.2 deg during patient handling, respectively. Conclusion: IMU use on trauma patients safely described H-N motion kinematics in a small sample of patients with different spectrums of illness during their care in the ED. Future studies utilizing IMUs could inform ED spine motion restriction protocols and compare movement of patients in specific subsets (intoxicated, spinal tenderness, injury severity etc.).